PRAME promotes invasion and metastasis of salivary adenoid cystic carcinoma by regulating RARα stability via the cullin2 ubiquitin‐proteasome system - Xudong Wang; Tingyao Ma; Yixin Jing; Tianyi Li; Xi Zhao; Guohan Zhao; Ran Gao; Lu Kong; Xiaohong Chen (Clinical and Translational Medicine, 2026)
Abstract Background All‐trans retinoic acid (ATRA) exerts its biological functions primarily through nuclear receptors, but its therapeutic efficacy in solid tumours remains limited. This study aimed to elucidate the regulatory role of the cancer‐testis antigen PRAME in posttranslational modifications (PTMs) of the ATRA receptor RARα, and to assess its consequent impact on tumour progression in salivary adenoid cystic carcinoma (SACC). Methods Transcriptome sequencing was performed on public datasets from the Gene Expression Omnibus (GEO) and on clinical tissue samples to identify overlapping differentially expressed genes. The expression pattern of PRAME across human pan‐cancer and its correlation with overall survival were analyzed using the TCGA database. Cellular transcriptome sequencing, cellular functional assays, co‑immunoprecipitation (Co‐IP), western blotting, protein stability assays, nude mouse xenograft tumour and lung metastasis models, and bioinformatic analyses were conducted to investigate the potential regulatory mechanism by which PRAME promotes metastasis in SACC through degradation of RARα and regulation of the EMT pathway. Results PRAME was found to be highly expressed in 33 common human tumour types, with minimal expression in normal tissues, and its upregulation correlated with poor prognosis. In SACC clinical specimens and cell lines, PRAME expression was significantly elevated. Functionally, PRAME upregulated Twist1 expression and promoted epithelial–mesenchymal transition, thereby enhancing the invasive and metastatic capabilities of SACC cells. In vivo, PRAME silencing attenuated subcutaneous tumorigenesis and pulmonary metastasis. Mechanistically, PRAME bound to the Cullin2 ubiquitin ligase complex, destabilizing RARα protein and promoting epithelial–mesenchymal transition (EMT). Conclusion Collectively, our findings reveal that PRAME drives SACC metastasis by accelerating RARα degradation through the Cullin2 ubiquitin–proteasome pathway while simultaneously inducing Twist1‐mediated EMT. These results position PRAME as a candidate biomarker and an actionable therapeutic target in SACC. Key points In salivary adenoid cystic carcinoma (SACC), PRAME drives tumour cell invasion and metastasis by upregulating Twist1 and inducing epithelial–mesenchymal transition. PRAME associates with the Cullin2 ubiquitin ligase to destabilize RARα, uncovering a posttranslational mechanism that may limit ATRA responsiveness in SACC. PRAME promotes subcutaneous tumour growth and pulmonary metastasis in vivo, consolidating its role as a key oncogenic driver in SACC.